The premise, promise, and perils of artificial intelligence in critical care cardiology - Huerta, Nicholas; Rao, Shiavax J.; Isath, Ameesh; Wang, Zhen; Glicksberg, Benjamin S.; Krittanawong, Chayakrit (Progress in cardiovascular diseases, 2024)
Artificial intelligence (AI) is an emerging technology with numerous healthcare applications. AI could prove particularly useful in the cardiac intensive care unit (CICU) where its capacity to analyze large datasets in real-time would assist clinicians in making more informed decisions. This systematic review aimed to explore current research on AI as it pertains to the CICU. A PRISMA search strategy was carried out to identify the pertinent literature on topics including vascular access, heart failure care, circulatory support, cardiogenic shock, ultrasound, and mechanical ventilation. Thirty-eight studies were included. Although AI is still in its early stages of development, this review illustrates its potential to yield numerous benefits in the CICU.